Potential for Nirsevimab use in Pakistan - Moaz, Muhammad; Hayat, Basum (Journal of the Pakistan Medical Association, 2025)
Respiratory Tract Infections can be classified as upper and lower tract infections. Upper tract infections are more common such as laryngitis and pharyngitis, but the infections of lower respiratory tract are more fatal such as influenza or bronchitis. Respiratory Syncytial Virus (RSV) is one of the major causes of acute lower respiratory tract infections and consequent admissions to hospital among young children. This virus belongs to paramyxoviridae family and is an RNA virus. It can cause a range of respiratory symptoms such as cold-like symptoms to more severe respiratory distress and complications such as bronchiolitis and pneumonia. It spreads through respiratory droplets when an individual infected with it, coughs, or sneezes. Preterm infants are highly susceptible to RSV infection due to weak immune system. A new study published in 20221 unveiled the use Nirsevimab for the avoidance of RSV in late preterm and term infants. When a single dose of this monoclonal antibody was administered before the RSV season, the incidence of RSV-associated lower respiratory tract infections was 70.1% lower than the placebo group. It has an extended half-life and has high efficacy against medically attended RSV-associated lower respiratory tract infections. Moreover, the safety profile of Nirsevimab and Palivizumab, another commonly prescribed antibody medication, were similar as indicated in a study of 20222. Moreover, a study indicated that single dose of Nirsevimab was enough to provide protection during a typical season of RSV which is a bright prospect in comparison to monthly doses of palivizumab.1 Pakistan is already an endemic country for viral infections this is further compounded by the fragility of its healthcare system, rendering this issue notably significant3. The characteristics of the virus in addition to the environmental conditions that favour its transmission contribute to its typical seasonal pattern. Another research study determined that outbreaks of respiratory viruses predominantly occur during the winter and early spring seasons, with a significant proportion of confirmed cases being admitted during the months of November, December, and January.4 Another study showed that RSV circulates all around the year in Karachi, Pakistan with prime time being the monsoon rains between July and September. RSV was responsible for almost 33% acute respiratory infections related hospitalizations in young infants in this study.5 ---Continue